Registration procedure for spatial correlation of physical energy deposition of particle irradiation and cellular response utilizing cell-fluorescent ion track hybrid detectors. (8th August 2016) - Niklas, M; Zimmermann, F; Schlegel, J; Schwager, C; Debus, J; Jäkel, O; Abdollahi, A; Greilich, S
Abstract: The hybrid technology cell-fluorescent ion track hybrid detector ( Cell-Fit-HD ) enables the investigation of radiation-related cellular events along single ion tracks on the subcellular scale in clinical ion beams. The Cell-Fit-HD comprises a fluorescent nuclear track detector (FNTD, the physical compartment), a device for individual particle detection and a substrate for viable cell-coating, i.e. the biological compartment. To date both compartments have been imaged sequentially in situ by confocal laser scanning microscopy (CLSM). This is yet in conflict with a functional read-out of the Cell-Fit-HD utilizing a fast live-cell imaging of the biological compartment with low phototoxicity on greater time scales. The read-out of the biological from the physical compartment was uncoupled. A read-out procedure was developed to image the cell layer by conventional widefield microscopy whereas the FNTD was imaged by CLSM. Point mapping registration of the confocal and widefield imaging data was performed. Non-fluorescent crystal defects ( spinels ) visible in both read-outs were used as control point pairs. The accuracy achieved was on the sub- µ m scale. The read-out procedure by widefield microscopy does not impair the unique ability of spatial correlation by the Cell-Fit-HD . The uncoupling will enlarge the application potential of the hybrid technology significantly. The registration allows for an ultimate correlation of microscopic physical beam parameters and cell kinetics on greater time scales. The method reported herein will be instrumental for the introduction of a novel generation of compact detectors facilitating biodosimetric research towards high-throughput analysis.